Use of budesonide in severe asthmatics aged 1-3 years. Issue 3 (September 1993) - Connett, G J; Warde, C; Wooler, E; Lenney, W
Abstract : The treatment of severe asthmatics aged 1-3 years with budesonide administered via Nebuhaler and Laerdal facemask was assessed in a six month, double blind, placebo controlled study. Patients were randomised to budesonide (n = 20) or placebo (n = 20) treatment. Daily symptom scores were recorded by parents and clinic visits occurred every six weeks. Cough scores improved significantly with budesonide: nocturnal and daytime cough scores (0-2) fell by a mean (SEM) of 0.4 (0.2) and 0.5 (0.2); while with placebo the nocturnal score increased by 0.1 (0.2) and daytime score was unchanged at 0.0 (0.2). All other data showed improvements for active over placebo treatment. Thirteen children in each group completed six months' treatment. Parents of 25 of these found the delivery system convenient and easy to use. While blinded to treatment it was assessed to be beneficial in nine of 13 receiving budesonide and four of 13 receiving placebo. The Nebuhaler and facemask is an acceptable delivery system for long term asthma treatment. Symptoms are significantly reduced when it is used to give 400-800 micrograms budesonide/day to children aged 1-3 years who cannot use other delivery systems.